Upaya Orang Tua Dalam Meningkatkan Disiplin Ibadah Salat Fardhu Pada Anak (Studi Kasus Kelas VIII Mts 1 Sambirejo Sragen) - Abdurrohman, al Farih, Drs. M. Darojat Ariyanto, M.Ag (2017)
Middle school children age which is a transition phase from children into adolescence is a phase which needs a strong religious basic from parents and teachers in the school. The obligatory prayer at that age children make parents should always provide supervision on the children worship. In MTs 1 Sambirejo Sragen is one of the secondary schools that implement the importance of prayer, especially at a zhuhur time. So how the efforts of parents in disciplining of prayer, more specifically of obligatory prayers after school. Based on the background and the formulation of the problem above, this is a survey-based research. This type of research requires researchers to look for valid and accurate data on the subject of research as required by researcher. So he can conclude the efforts of parents to including student discipline obligatory in prayers at MTs1 Sambirejo Sragen. After conducting research to establish the discipline of prayer in children, applymy the parents make some efforts including: habituation, exemplary, awareness, and supervision. Factors supporting the discipline of prayer for children, among others are: family, environment, education, and association. Family and education become the dominant factors affecting the formation of the discipline of children prayer. The success of parents in instilling children player discipline can be seen through their behaviors towards their prayers, among others: praying on time, responsibility, and have the desire to pray without orders. Keywords: habituation, examplary, awareness, and supervision